Escape [compact disc, unabridged] - Patterson, James, 1947-; Ellis, David, 1967- (Patterson, James, 1947- Black book thriller., 2022)
As Chicago's special-ops leader Detective Billy Harney knows well, money is not the only valuable currency. The billionaire he's investigating is down to his last twenty million. But he's also being held in jail. For now. Billy's unit is called to the jail when six inmates escape, and two others are missing. Two correctional officers are dead. Approaching the scene, Billy spots something in an empty lot. Two Kevlar vests. Two helmets. Two assault rifles. And a handwritten note: Hi, Billy, having fun yet?